2020
DOI: 10.21106/ijma.294
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Ultrasound Use in Low and Middle Income Countries: A Systematic Review

Abstract: Background: Evidence on recent trends regarding the impact and cost-benefits of ultrasound in resource-constrained settings is limited. This study presents a systematic review to determine recent trends in the utility and applicability of ultrasound use in low and middle income countries (LMIC). The review includes characterizing and evaluating trends in (1) the geographic and specialty specific use of ultrasound in LMICs, (2) the innovative applications and the accompanying research findings, and (3) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 48 publications
0
67
0
4
Order By: Relevance
“… 73 However, with the availability of smaller and cheaper devices and a growing body of evidence, wider use of LUS can be foreseen. 74 , 75 Although cost-effectiveness studies in LMICs are lacking, LUS has been shown to reduce the use of CXR and chest CT in resource-rich ICUs, with less radiation exposure and lower costs. 76 , 77 …”
Section: Questionsmentioning
confidence: 99%
“… 73 However, with the availability of smaller and cheaper devices and a growing body of evidence, wider use of LUS can be foreseen. 74 , 75 Although cost-effectiveness studies in LMICs are lacking, LUS has been shown to reduce the use of CXR and chest CT in resource-rich ICUs, with less radiation exposure and lower costs. 76 , 77 …”
Section: Questionsmentioning
confidence: 99%
“…Additionally to known benefits, ultrasound (LUS in particular) can be readily learned by a variety of medical professionals, not just radiological, to allow for rapid assessment and treatment in a variety of settings. Ultrasound devices can be used by a single operator, handheld, and can provide diagnostic capabilities at a much lower cost than other imaging tools such as CT or magnetic resonance imaging (MRI) and, in rural regions of LMICs, also compared with to traditional radiology [ 45 ]. These features make ultrasound an attractive option for clinical use in LMICs for both inpatient and outpatient use.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the diagnostic utility of ultrasound in the medical, surgical, and obstetric fields in LMICs [ 46 , 47 ]. This has led to the increase in point-of-care ultrasound (POCUS) in LMICs [ 45 ], which is done by the doctor in real time and at the bedside [ 48 ]. Studies have shown that doctors and other healthcare professionals can perform effective and accurate scans after 3 h of teaching and about 5 h of practice [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review examining the trends in the use of POCUS in LMICs found the number of countries reporting use of ultrasound had grown from 50 to 62, with 70% of the included studies originating from Southeast Asia or sub-Saharan Africa. 35 In addition, studies have demonstrated that POCUS skills can be effectively taught to both physicians and nonphysician clinicians in resource-limited settings. 36 , 37 It remains to be seen if POCUS has the ability to effectively improve patient outcomes, although a single-center study from Tanzania demonstrated that POCUS resulted in earlier initiation of therapy, ranging widely from initiation of antibiotics to use of anticoagulants to surgical intervention, due to more rapid and accurate diagnosis.…”
Section: Questionsmentioning
confidence: 99%